Faldaprevir combined with pegylated interferon alfa‐2a and ribavirin in treatment‐naïve patients with chronic genotype1 HCV: SILEN‐C1 trial12. Issue 6 (12th June 2013) - Sulkowski, Mark S.; Asselah, Tarik; Lalezari, Jacob; Ferenci, Peter; Fainboim, Hugo; Leggett, Barbara; Bessone, Fernando; Mauss, Stefan; Heo, Jeong; Datsenko, Yakov; Stern, Jerry O.; Kukolj, George; et al.
Abstract Faldaprevir (BI 201335) is a potent, hepatitis C virus (HCV) NS3/4A protease inhibitor with pharmacokinetic properties supportive of once‐daily (QD) dosing. Four hundred and twenty‐nine HCV genotype (GT)‐1 treatment‐naïve patients without cirrhosis were randomized 1:1:2:2 to receive 24 weeks of pegylated interferon alfa‐2a and ribavirin (PegIFN/RBV) in combination with placebo, faldaprevir 120 mg QD with 3 days of PegIFN/RBV lead‐in (LI), 240 mg QD with LI, or 240 mg QD without LI, followed by an additional 24 weeks of PegIFN/RBV. Patients in the 240 mg QD groups achieving maintained rapid virologic response (mRVR; viral load [VL] <25 IU/mL at week 4 and undetectable at weeks 8‐20) were rerandomized to cease all treatment at week 24 or continue receiving PegIFN/RBV up to week 48. VL was measured by Roche TaqMan. Sustained virologic response (SVR) rates were 56%, 72%, 72%, and 84% in the placebo, faldaprevir 120 mg QD/LI, 240 mg QD/LI, and 240 mg QD groups. Ninety‐two percent of mRVR patients treated with faldaprevir 240 mg QD achieved SVR, irrespective of PegIFN/RBV treatment duration. Eighty‐two percent of GT‐1a patients who received faldaprevir 240 mg QD achieved SVR versus 47% with placebo. Mild gastrointestinal disorders, jaundice resulting from isolated unconjugated hyperbilirubinemia, and rash or photosensitivity were more common in the active groups than with placebo. Discontinuations resulting from adverse events occurred in 4%, 11%, and 5% of patients treated with 120 mg QD/LI, 240 mg QD/LI, and 240 mg QD of faldaprevir versus 1% with placebo. Conclusion: Faldaprevir QD with PegIFN/RBV achieved consistently high SVR rates with acceptable tolerability and safety at all dose levels. The 120 and 240 mg QD doses are currently undergoing phase 3 evaluation. (HEPATOLOGY 2013;57:2143–2154)